Pulmonary Tuberculosis Diagnosis Practices - Muhammad Khurram , Qaiser Aziz , Shamaila Mumtaz ,Muhammad Faheem , Hamama Tul Bushra . (Journal of Rawalpindi Medical College, 2014)
Background: To study pulmonary tuberculosis (TB) diagnosis practices. Methods: In this cross sectional study, 364 newly diagnosed pulmonary TB patients were included. Patients were categorized into four groups i.e. clinical, radiological, clinical and radiological and definitive pulmonary tuberculosis cases (clinical, radiological and sputum smear examination/mycobacterium TB culture). Results: Of the 364 patients, 35.1% were diagnosed on clinical and radiological basis, 26.37% in definite way, 20.8% on radiological, and 17.58% on clinical evaluation. Sputum smear examination for Mycobacterium tuberculosis was sought in 85.6% patients, of these 31.9% were positive. In definite cases category, AFB smear were positive in 95.8% patients (p value <0.0000001) as compared to other three categories clinical 9.4%, radiological 0% and clinical and radiological 3.2%. Conclusion: Diagnosis of pulmonary TB is most frequently based on clinical and radiological features rather than results of microbiological evaluation.